N-(3,4-Dimethylphenyl)benzenesulfonamide - John, P.; Sharif, S.; Khan, I.U.; Khizar, S.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The structure of the title compound, C(14)H(15)NO(2)S, shows the sulfonamide N atom to be approximately perpendicular to the plane through the S-bound benzene ring [the N-S-C-C torsion angle is -87.4 (3)degrees] and to lie to the opposide side of this ring to the two sulfonamide O atoms. The N-bound benzene ring is splayed out with respect to the rest of the molecule so that overall, the molecule adopts a twisted conformation. The dihedral angle between the two benzene rings is 64.5 (3)degrees. In the crystal, supramolecular chains aligned along the b axis are formed via N-H...O hydrogen bonds.